Relevansi Penguasaan Bahasa Arab dalam Penafsiran Nushush Fiqh Munakahat Studi Hukum Keluarga Islam Kontemporer (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Mastery of the Arabic language plays a crucial role in understanding and interpreting the nushush of fiqh munakahat, which is an integral part of Islamic family law. In the context of contemporary Islamic family law, a deep understanding of the Arabic language can affect the accuracy of interpretation and application of the law as a whole. Nushush fiqh munakahat often contain technical terms, complex grammatical structures and contextual meanings that can only be properly understood through a good command of Arabic. This study aims to explore the relevance of mastering Arabic in the interpretation of the nushush of fiqh munakahat by examining the various challenges, interpretative errors, and legal implications that can arise from weak linguistic skills. This study is conducted through a qualitative approach with a literature study of primary and secondary sources in fiqh munakahat. The results of this study are expected to contribute to strengthening the method of interpretation of Islamic law, especially in the field of munakahat, as well as encouraging the improvement of Arabic language competence for practitioners and academics of Islamic law.